Kepemimpinan Non-Muslim: Penafsiran Surat Al-Maidah Ayat 51 dalam Tafsir Al-Azhar dan Tafsir Al-Mishbah - Muhammad Wahyudi (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2018)
This article wants to explain the interpretation of Surah Al-Maidah Verse 51 in two interpretive books, namely Tafsir Al-Azhar written by Haji Abdul Karim Malik Amrullah (Hamka) and Tafsir Al-Mishbah by M. Quraish Syihab. This text wants to compare the perspectives in the interpretation of the two of Surat Al-Maidah Verse 51 regarding non-Muslim leadership. Both models of interpretation deserve to be studied and relevant because both write their tafisr books based on the tahlili (analytical) method, which is to interpret the verses of the Koran by describing various aspects contained in the verses being interpreted and explaining the meanings. the meaning it entails. In addition, these two tafsir books have the same style of interpretation as adabi ijtima'i, a style that describes and describes the interpretation based on social facts. This article concludes that Hamka interprets Surah Al-Maidah verse 51 as an absolute prohibition against making non-Muslims as leaders among Muslims. He argued that non-Muslims would always try to do bad things to Muslims. Meanwhile, M. Quraish Shihab interprets this verse not as an absolute prohibition. Non-Muslims who live in peace with Muslim communities have the same rights and obligations as Muslims, as well as the right to become leaders.